2021
DOI: 10.3171/2021.2.spine201879
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty on patient-reported outcomes after elective thoracolumbar degenerative spine surgery

Abstract: OBJECTIVE Frailty has been shown to be a risk factor of perioperative adverse events (AEs) in patients undergoing various types of spine surgery. However, the relationship between frailty and patient-reported outcomes (PROs) remains unclear. The primary objective of this study was to determine the impact of frailty on PROs of patients who underwent surgery for thoracolumbar degenerative conditions. The secondary objective was to determine the associations among frailty, baseline PROs, and perioperative AEs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In the field of spine surgery, various iterations of frailty, specifically the modified frailty index (mFI), have been effective tools for predicting postoperative adverse surgical events, morbidity, and mortality [8][9][10][11]. However, most of these studies have primarily examined patients undergoing anterior cervical or thoracolumbar procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of spine surgery, various iterations of frailty, specifically the modified frailty index (mFI), have been effective tools for predicting postoperative adverse surgical events, morbidity, and mortality [8][9][10][11]. However, most of these studies have primarily examined patients undergoing anterior cervical or thoracolumbar procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a syndrome characterized by decreased physiological reserve, daily activities and strength. 10 , 11 Accurate risk stratification and prediction of postoperative complications over time are imperative in older patients undergoing lumbar fusion surgery. 12 Many studies have reported convincing results inn recent years that frailty is a stronger predictor than age for postoperative morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a syndrome of decreased physiological reserve, daily activities as well as strength [10,11].…”
Section: Introductionmentioning
confidence: 99%